Perceptions and Practice: an Anthology of Impact Assessment Experiences - Norrish, Patricia; Sayce, Kay (Technical Centre for Agricultural and Rural Cooperation, 2006)
This book of stories on impact assessment, written by a journalist/editor, with guidance from an experienced development practitioner, is illustrative of CTA’s efforts to promote a culture of organisational learning...